Length‐weight relationships of six fishes from the Anning River, China. (1st December 2017) - Ru, H. J.; Zhang, Y.; Li, Y. F.; Wu, X. X.; Ni, Z. H.
Summary: This paper provides the length–weight relationships for six fish species collected from the Anning River, one of the biggest tributaries of the Yalong River in China. A total of 1096 specimens belonging to six fish species were analyzed. Among them, the length–weight relationships for 4 fish species are first‐time reports for FishBase and new maximum lengths of one fish species is also reported.